2007
DOI: 10.1504/ijtg.2007.012361
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary game between tourist and resident populations and Tourist Carrying Capacity

Abstract: Tourism implies the encounter and interaction of two non-homogeneous populations, possibly further internally structured into like-minded communities. Its sustainability, although still poorly defined, depends upon the type of such interaction and its evolution. This is why we believe that the theoretical representation of the problem has to occur within a game theory framework. This paper begins to investigate this uncharted, perhaps novel, idea. Moreover, building on existing literature, it discusses the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 8 publications
0
29
0
2
Order By: Relevance
“…Existing studies cover topics including integration in TSCs (Theuvsen, 2004;Lafferty & Fossen, 2001); competition issues related to hotels (Chung, 2000;García & Tugores, 2006;Mazzeo, 2002), tour operators (Baum & Mudambi, 1994;Taylor, 1996;Caccomo & Solonandrasana, 2001), and attractions (Wie, 2004(Wie, , 2005Candela & Cellini, 2006); relationships between the local government and tourism organizations (Piga, 2003a(Piga, , 2003b(Piga, , 1999Accinelli et al, 2006a), tour operators and destinations (Baloglu & Mangaloglu, 2001;Carey et al, 1997;Curtin & Busby, 1999;Klemm & Parkinson, 2001), and tourism organizations and tourists (Taylor, 1998;Han et al, 2004); and the evolutionary relationships between tourists and residents (Accinelli et al, 2006b;Bimonte & Punzo, 2007).…”
Section: Two-party Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies cover topics including integration in TSCs (Theuvsen, 2004;Lafferty & Fossen, 2001); competition issues related to hotels (Chung, 2000;García & Tugores, 2006;Mazzeo, 2002), tour operators (Baum & Mudambi, 1994;Taylor, 1996;Caccomo & Solonandrasana, 2001), and attractions (Wie, 2004(Wie, , 2005Candela & Cellini, 2006); relationships between the local government and tourism organizations (Piga, 2003a(Piga, , 2003b(Piga, , 1999Accinelli et al, 2006a), tour operators and destinations (Baloglu & Mangaloglu, 2001;Carey et al, 1997;Curtin & Busby, 1999;Klemm & Parkinson, 2001), and tourism organizations and tourists (Taylor, 1998;Han et al, 2004); and the evolutionary relationships between tourists and residents (Accinelli et al, 2006b;Bimonte & Punzo, 2007).…”
Section: Two-party Relationshipsmentioning
confidence: 99%
“…A better understanding of such relationships in TSCs would be very helpful for tourism decision makers to achieve efficient and effective TSCM. The research reviewed in Section 3.2 (i.e., Accinelli et al, 2006b;Bimonte & Punzo, 2007) has already investigated the evolution passes of the interactions between tourists and residents in a destination. More in-depth analysis of TSC dynamics is necessary in the future.…”
Section: Tsc Dynamicsmentioning
confidence: 99%
“…Ballantyne et al believed that environmental education could be bridge that helps to bring out a positive attitude from tourists towards the environment [43].Castellani & Sala has identified that in measuring and assessing carrying capacity behavioural intention and characteristics of the tourists is an important factor to be considered [8]. Carrying capacity in tourism is the maximum number or threshold value which can be accepted or accommodated by a tourist destination while maintaining tourists satisfaction with reference to a standard of quality [8,16,44]. Hence, it is important to include environment education and carrying capacity in sustainable tourism management policy.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Indeed, tourism is the encounter of two heterogeneous communities, the local and the tourist communities (which could actually be more than two, as they are not monolithic bodies -see the analysis carried out in Bimonte and Punzo [23]), each having different needs, interests, and expectations with regard to tourism resources (Hardy et al [6]; Williams [24]). A shared vision or common management regarding their use is therefore required to avoid locals entering into turbulent competition with tourists.…”
Section: About Sustainability In Tourismmentioning
confidence: 99%
“…A shared vision or common management regarding their use is therefore required to avoid locals entering into turbulent competition with tourists. Conflicts, in turn, reduce the quality of tourists' experience and, probably, their willingness to pay (WTP) (Bimonte and Punzo [23]). These aspects are exacerbated by the fact that most tourism resources share the characteristics of "public goods" and/or "common pool resources" (CPRs).…”
Section: About Sustainability In Tourismmentioning
confidence: 99%